2022
DOI: 10.3390/nu14183737
|View full text |Cite
|
Sign up to set email alerts
|

From Diabetes Care to Heart Failure Management: A Potential Therapeutic Approach Combining SGLT2 Inhibitors and Plant Extracts

Abstract: Diabetes is a complex chronic disease, and among the affected patients, cardiovascular disease (CVD)is the most common cause of death. Consequently, the evidence for the cardiovascular benefit of glycaemic control may reduce long-term CVD rates. Over the years, multiple pharmacological approaches aimed at controlling blood glucose levels were unable to significantly reduce diabetes-related cardiovascular events. In this view, a therapeutic strategy combining SGLT2 inhibitors and plant extracts might represent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 110 publications
1
5
0
Order By: Relevance
“…Moreover, in an in vivo study on mice fed a high-fat diet, it has been demonstrated that luteolin shows anti-obesity properties, decreases the body and epididymal fat weight and improves vascular dysfunction, by inhibiting the ROS and TNF-α action [ 109 ]. This is in also in accordance with our previous studies showing that, polyphenols improve dyslipidaemia in NAFLD [ 26 , 110 , 111 , 112 , 113 ].…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, in an in vivo study on mice fed a high-fat diet, it has been demonstrated that luteolin shows anti-obesity properties, decreases the body and epididymal fat weight and improves vascular dysfunction, by inhibiting the ROS and TNF-α action [ 109 ]. This is in also in accordance with our previous studies showing that, polyphenols improve dyslipidaemia in NAFLD [ 26 , 110 , 111 , 112 , 113 ].…”
Section: Discussionsupporting
confidence: 94%
“…Likewise, it cannot provide significant protection against CAD, MI, LAS, and CES, which are triggered by insufficient perfusion due to vascular occlusion. Another potential reason for the difference in results could be that one of the main contributors of dried fruits to reduce CVD risk is to improve glucose tolerance and insulin sensitivity and then to regulate lipid and glucose metabolism, which requires a long-term process ( 41 ). Thus dried fruit was more protective against chronic diseases with less severe lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, if supplementation with ketone supplements, for example, leads to an acute elevation of β-OHB in the blood, it can significantly increase activation of caspase-1 and increase secretion of the proinflammatory cytokine IL-1β in whole blood ( 161 163 ). Multiple studies ( 120 , 164 ) have shown that in patients with T2D combined with CVD, SGLT2 inhibitors significantly inhibit NLRP3 inflammasome activation and IL-1β secretion in human macrophages by increasing serum β-OHB levels and decreasing serum insulin, glucose, and uric acid levels.…”
Section: The Role Of An Sglt2 Inhibitor On the Nlrp3 Inflammasome: Po...mentioning
confidence: 99%